4D Micro-Computed X-ray Tomography as a Tool to Determine Critical Process and Product Information of Spin Freeze-Dried Unit Doses - Brecht Vanbillemont; Joris Lammens; Wannes Goethals; Chris Vervaet; Matthieu N. Boone; Thomas De Beer (MDPI AG, 2020)
Maintaining chemical and physical stability of the product during freeze-drying is important but challenging. In addition, freeze-drying is typically associated with long process times. Therefore, mechanistic models have been developed to maximize drying efficiency without altering the chemical or physical stability of the product. Dried product mass transfer resistance ( <semantics> R p </semantics> ) is a critical input for these mechanistic models. Currently available techniques to determine <semantics> R p </semantics> only provide an estimation of the mean <semantics> R p </semantics> and do not allow measuring and determining essential local (i.e., intra-vial) <semantics> R p </semantics> differences. In this study, we present an analytical method, based on four-dimensional micro-computed tomography (4D- <semantics> μ </semantics> CT), which enables the possibility to determine intra-vial <semantics> R p </semantics> differences. Subsequently, these obtained <semantics> R p </semantics> values are used in a mechanistic model to predict the drying time distribution of a spin-frozen vial. Finally, this predicted primary drying time distribution is experimentally verified via thermal imaging during drying. It was further found during this study that 4D- <semantics> μ </semantics> CT uniquely allows measuring and determining other essential freeze-drying process parameters such as the moving direction(s) of the sublimation front and frozen product layer thickness, which allows gaining accurate process knowledge. To conclude, the study reveals that the variation in the end of primary drying time of a single vial could be predicted accurately using 4D- <semantics> μ </semantics> CT as similar results were found during the verification using thermal imaging.